2011
DOI: 10.1186/1756-3305-4-69
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of canine Leishmania infantum infection in western China detected by PCR and serological tests

Abstract: BackgroundCanine leishmaniasis (CanL) is endemic in western China, resulting in important public health problem. It is essential to evaluate the prevalence of canine Leishmania infantum infection for designing control policy. In the present study we report for the first time prevalence of Leishmania infection in dogs living in Jiuzhaigou County (Sichuan Provence, China), which is not only an important endemic area of CanL but also a tourism scenic spot, detected by PCR, ELISA and dipstick test. The results cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
65
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 48 publications
4
65
2
Order By: Relevance
“…Therefore, the two canine isolates and the other six Chinese isolates are suggested to be L. infantum in this study. Since the canine isolate WenChuan was from Sichuan, this result indicated that the canine leishmaniasis (CanL) in Sichuan may be caused by L. infantum, which is consistent with the recent studies (Shang et al 2011;Wang et al 2011). Moreover, considering the infected dogs are the main reservoir host of human VL, L. infantum should be the causative agents of VL in Sichuan province.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, the two canine isolates and the other six Chinese isolates are suggested to be L. infantum in this study. Since the canine isolate WenChuan was from Sichuan, this result indicated that the canine leishmaniasis (CanL) in Sichuan may be caused by L. infantum, which is consistent with the recent studies (Shang et al 2011;Wang et al 2011). Moreover, considering the infected dogs are the main reservoir host of human VL, L. infantum should be the causative agents of VL in Sichuan province.…”
Section: Discussionsupporting
confidence: 91%
“…29,30 kDNA is considered the most sensitive target for leishmaniasis diagnosis, because it contains ∼10,000 minicircles per parasite. 31 Samples that were positive based on PCR and/ or real-time PCR, but negative based on rK39 ICT, might have a low infection burden and, therefore, lower levels of anti-Leishmania antibodies, consistent with previous studies 32,33 in which some seronegative dogs were PCR positive. In our study, we observed one serologically positive dog that was negative for Leishmania DNA.…”
Section: Discussionsupporting
confidence: 77%
“…Based on extensive surveys from 1951 to 1959 (22), canine leishmaniasis of domestic dogs was reported in the adjacent regions of Beijing with landscapes similar to those in Liaoning, Hebei, Shandong, and other adjacent provinces in northeastern China (5-8, 21) ( Table 2). The rate of incidence in dogs expressed as percentage of infection was modest, but it was higher in the north, e.g., northern Hebei (19/146 ϭ 13%) and Liaoning (11/ 539 ϭ 2%), and very low in the south, e.g., Shandong (34/3,100 ϭ 0.1%) and southern Hebei (0/1,125 ϭ 0%) (18,19,22). In these regions, there has since been no report of either human VL or canine VL in domestic dogs.…”
Section: Types Distribution and Current Status Of Visceral Leishmanmentioning
confidence: 99%
“…The principal reservoirs are domestic dogs, which are thought to acquire infection originally from canids of the sylvatic cycle (16,17). Canine leishmaniasis has been reported at high rates in the western region, e.g., 59.43% (63/106) in Sichuan province and 77.21% (61/79) in Gansu province when surveyed in 2011 and 2006, respectively (18,19).…”
Section: Types Distribution and Current Status Of Visceral Leishmanmentioning
confidence: 99%